Problems of rice breeding in West Africa: paper presented at the WARDA Seminar on Rice Breeding and Varietal Improvement, 15th January, 1973 - Abifarin, A.O. (1973)
Different types of problems are to be tackled by West African breeders to make important improvement on the West African varieties. The most important are those that directly concern the morphology and physiology of the rice varieties. The first major change should be the reduction in height, and production of shorter and narrower leaves. Different maturity ranges are required to satisfy the rain patterns and ecology of a particular area. The morphological and physiological problems are to be considered with the ecological problems for rice cultivation. The problem of pests and diseases in West Africa are also of major concern. Stemborers, blast and bird attack are the most important. There is a need for breeding for long grain types. This creates some problems as this traits has to be combined with the high head rice recovery, high amylose, high protein content, grain translucency and good cooking quality.